Beneficial effect of D‐allose for isolated islet culture prior to islet transplantation. (26th November 2015) - Kashiwagi, Hirotaka; Asano, Eisuke; Noguchi, Chisato; Sui, Li; Hossain, Akram; Akamoto, Shintaro; Okano, Keiichi; Tokuda, Masaaki; Suzuki, Yasuyuki
Abstract: Background: Pretransplant restoration of islets damaged during isolation remains to be solved. In this study, we examined the effect of D‐allose on islets isolated from rat pancreata prior to islet transplantation. Methods: Rat islets isolated from fresh pancreata were cultured overnight in Roswell Park Memorial Institute 1640 solution in the absence (group 1) or presence (group 2) of D‐allose. Then we assessed stimulation index of insulin, and cure rate after islet transplantation to diabetic nude mice. We also measured malondialdehyde level and caspase 3 activity of islets after the overnight culture for assessment of the oxidative stress and the apoptosis. Results: D‐allose significantly improved insulin secretion of islets. The stimulation index in group 2 was significantly higher than in group 1. Cure rate after transplantation in group 2 was higher than in group 1 especially in the first week. The malondialdehyde level in group 2 was significantly lower than in group 1. But the caspase 3 activities in both groups did not differ. Conclusions: D‐allose treatment of isolated islet culture prior to transplantation restored islet function and increased successful transplant rate. The results of this study suggested that D‐allose improved function of damaged islets through its anti‐oxidative activity. Abstract : Highlight Islet recovery is of great importance for successful transplantation. The rare sugar D‐allose, a glucose isomer, dissolved in culture medium, increased the cure rate after islet transplantation to diabetic nude mice. Kashiwagi and colleagues conclude that D‐allose repaired islet damage from ischemia‐reperfusion injury in isolation steps through its anti‐oxidative activity.